OpenEHR logic module: a tool for creating decision rules - Silva, Beatriz (2024)
In clinical decision-making, data are fundamental elements for extracting knowledge for knowledge-based systems. Clinical Decision Support Systems (CDSS) need to ensure that stored data are semantically interoperable to, in turn, represent clinical knowledge and improve the quality of healthcare delivery. The openEHR standard provides a set of specifications that allow health information systems to manage electronic health records in a structured and standardized format. Therefore, this article aims to present a decision support tool capable of creating decision rules, including rules, decision tables, and scores. based on the decision language specifications of the openEHR.